Evaluation of Five Wheat Varieties on Arsenic Contaminated Soils of Bangladesh - Kamrozzaman, M.M.; Khan, M.A.H.; Ahmed, S.; Sultana, N.; Quddus, A.F.M. Ruhul (International Journal of Applied Sciences and Biotechnology, 2016)
An experiment was conducted at Farming System Research and Development Site, Hatgobindapur, Faridpur during 2012-13 to evaluate five wheat varieties against arsenic contaminated soils and determined accumulation of arsenic in grain and straw of wheat varieties. The experiment was laid out in RCB design with six replications. BARI Gom-21, BARI Gom-23, BARI Gom-24, BARI Gom-25 and BARI Gom-26 were used as treatment variables. The arsenic content was determined by using atomic absorption spectrophotometer (AAS). Result revealed that, wheat varieties differed in their grain arsenic concentration (0.49-1.15 mg kg-1). The arsenic translocation in wheat grains usually least and accumulation by different tissues followed the order root>stem>leaf>grain across the varieties. The variety BARI Gom-26 was found to accumulate least arsenic in grains followed by BARI Gom-25 and BARI Gom-24 under same growing condition due to phyto-extraction or phyto-morphological potential of the varieties. Maximum grain yield (4.36 t ha-1) was obtained from BARI Gom-26 followed by BARI Gom-25 and the lowest yield (3.43 t ha-1) was recorded from BARI Gom-23. Therefore, BARI Gom-26 and BARI Gom-25 can successfully be grown for higher yield in arsenic contaminated soils and water of Faridpur. Int J Appl Sci Biotechnol, Vol 4(3): 330-337